Recurrence Free Survival and Patterns of Recurrence in Pancreatic Ductal Adenocarcinoma: An Institutional Perspective - Saqib Raza Khan, Muhammad Tariq, Yasmin Abdul Rashid, Samad Jehangir Shah, Muhammad Nauman Zahir, Adnan Abdul Jabbar, Munira Moosajee, Muhammad Afzal, Salman Soomar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine recurrence-free survival, patterns of loco-regional and systemic recurrence in patients with pancreatic adenocarcinoma. Methods: We conducted a retrospective Study at the Department of Oncology in a tertiary care Hospital, Karachi Pakistan from January 2013 to December 2019. We studied the sample size of 67 adults of 18 to 70 years of age, diagnosed with adenocarcinoma of the pancreas and treated primarily with curative intent. All patients received complete treatment for the primary disease in our institution and data was extracted retrospectively from the hospital's medical record. Records were reviewed for recurrence of disease and patterns of loco regional and systemic recurrence. SPSS version 23 was used to analyze the data. Results: Out of 67 patients with pancreatic adenocarcinoma, 65 patients (97%) had a complete clinical and radiological response on the follow up scans performed at three months after the completion of curative treatment. However 2 (3%) patients had disease recurrence/residual disease on first follow up scan. Subsequent follow ups showed cancer recurrence was observed in 60 (89.5%) patients, out of which 10 (14.9%) had loco regional while 7 (10.5 %) had systemic only recurrence. Most of the patients (n= 43; 64.1%) had systemic as well loco regional recurrences. The most frequent site of distant metastasis was the liver (66 %). The median recurrence free survival was 09 months (IQR= 8, 15). Conclusion: This retrospective analysis highlights the patterns of recurrence after curative treatment of pancreatic ductal adenocarcinoma and indicates high recurrence rates which is expected for an aggressive disease like pancreatic carcinoma. By better understanding the patterns of recurrence, it can help in identifying subsets of patients with high risk of recurrence as well as in managing such patients more effectively.